2010
DOI: 10.1111/j.1468-2397.2009.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Childcare: welfare or investment?

Abstract: Conley A. Childcare: welfare or investment? Int J Soc Welfare 2010: 19: 173–181 © 2009 The Author, Journal compilation © 2009 Blackwell Publishing Ltd and the International Journal of Social Welfare. Childcare (also called day care or preschool) has generally served three purposes: to care for children while parents are employed; to provide early childhood education; and to cater to the needs of poor and disadvantaged children. This article proposes that the welfare approach to childcare be augmented by a soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(42 reference statements)
2
1
0
Order By: Relevance
“…Our findings corroborate other research demonstrating that child care provides staff and parents, including low-income households receiving government tuition vouchers, the opportunity to financially support their households while contributing in other ways to the local economy ( Conley, 2010 ; Scarr & Eisenberg, 1993 ). For working parents, we found that safe, reliable, and trusted child care programs allowed them to productively work and participate in their community.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings corroborate other research demonstrating that child care provides staff and parents, including low-income households receiving government tuition vouchers, the opportunity to financially support their households while contributing in other ways to the local economy ( Conley, 2010 ; Scarr & Eisenberg, 1993 ). For working parents, we found that safe, reliable, and trusted child care programs allowed them to productively work and participate in their community.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, child care is perceived to be an essential infrastructure that mutually benefits children, parents, families, staff, and the community. Our findings support existing evidence regarding the broader impacts of child care beyond children and the vital role child care plays in society ( Bayham & Fenichel, 2020 ; Conley, 2010 ; Scarr & Eisenberg, 1993 ; Temple & Reynolds, 2015 ). Further investigations into the value of child care for diverse populations will be an essential addition to the growing evidence that supports significant investments in the child care industry.…”
Section: Discussionsupporting
confidence: 87%
“…Affordable and high quality day care as in the European employment strategy also have an impact on the participation level, especially for women, and thus also be part of the active labour market policy, e.g. points to the discussion on whether child care should be seen as an expenditure or social investment [10]. In the Nordic countries childcare is universal and well developed, and will therefore not be further included in the analysis.…”
Section: Active Labour Market Policymentioning
confidence: 99%
“…Menurut (Scarr & Eisenberg, 1993) terdapat 3 tujuan penting dari TPA, Pertama Pengasuhan subtitusi bagi anak selama orangtuanya bekerja, Kedua program pendidikan untuk mengembangkan emosional dan kognitif anak, serta Ketiga intervensi untuk membantu anak dari keluarga tidak mampu. Sedangkan (Conley, 2010) menyebutkan TPA bukan hanya tempat penitipan anak saja akan tetapi TPA memiliki fungsi sebagai tempat pengasuhan dan pendidikan bagi anak usia dini, sebagai program untuk pemberian stimulus bagi perkembangan anak, baik dari segi motorik, kognitif, emosi, sosial dan moral melalui bermain. Selaras dengan pendapat tersebut hasil penelitian (Finch, Johnson, dan Phillips 2015, Gunawan 2016, Huston, Bobbitt, dan Bentley 2015 menunjukan bahwa TPA memiliki peran yang penting dalam perkembangan anak seperti anak menunjukan perilaku sosial yang baik, lebih sedikit terlibat masalah, berperan besar dalam pengembangan kemampuan kontrol diri seorang anak dan dapat mengembangkan kemampuan bahasa serta berbicara anak sesuai dengan tahapannya.…”
unclassified